A COMBINED MULTI-ANALYTICAL APPROACH FOR THE STUDY OF ROMAN GLASS FROM SOUTH-WEST IBERIA: SYNCHROTRON micro-XRF, EXTERNAL-PIXE/PIGE AND BSEM–EDS - SCHIAVON, N. (2013)
An integrated, multi-analytical approach combining the high sensitivity of SR-mXRF, the light element capability of PIXE/PIGE under a helium flux and the spatial resolution of BSEM + EDS was used to characterize chemical composition and corrosion of glass samples(first to fourth centuries AD) from an important, but scarcely investigated, Roman region of south-west Iberia (southern Portugal). The geochemical trends and associations of major, minor and trace elements were investigated to shed light on production techniques, the provenance of raw materials and decay mechanisms. The results, while confirming a production technique common to Roman glasses throughout the Empire—that is, a silica-soda-lime low-Mg, low-K composition, with glass additives as colouring and/or decolouring agents (Fe,Cu, Mn, Sb)—show at one site high Zr–Ti contents, suggesting a more precise dating for these glasses to the second half of the fourth century. The Ti–Fe–Zr–Nb geochemical correlations in the pristine glass indicate the presence of minerals such as ilmenite, zircon, Ti-rich Fe oxides and columbite in the sands used as raw materials for the glass former: these minerals are typical of granitic-type source rocks. The unusually high K content in the corrosion layers is consistent with burial conditions in K-rich soils derived from the alteration of 2:1 clays in K-bearing rock sequences.